Metabolic Abnormalities, Dietary Risk Factors and Nutritional Management in Amyotrophic Lateral Sclerosis - D’Amico, Emanuele (Nutrients, 2021)
Amyotrophic Lateral Sclerosis (ALS) is a devastating progressive neurodegenerative disease that affects motor neurons, leading to a relentless paralysis of skeletal muscles and eventual respiratory failure. Although a small percentage of patients may have a longer survival time (up to 10 years), in most cases, the median survival time is from 20 to 48 months. The pathogenesis and risk factors for ALS are still unclear: among the various aspects taken into consideration, metabolic abnormalities and nutritional factors have been the focus of recent interests. Although there are no consistent findings regarding prior type-2 diabetes, hypercholesterolemia and ALS incidence, abnormalities in lipid and glucose metabolism may be linked to disease progression, leading to a relatively longer survival (probably as a result of counteract malnutrition and cachexia in the advanced stages of the disease). Among potential dietary risk factors, a higher risk of ALS has been associated with an increased intake of glutamate, while the consumption of antioxidant and anti-inflammatory compounds, such as vitamin E, n-3 polyunsaturated fatty acids, and carotenoids, has been related to lower incidence. Poor nutritional status and weight loss in ALS resulting from poor oral intake, progressive muscle atrophy, and the potential hypermetabolic state have been associated with rapid disease progression. It seems important to routinely perform a nutritional assessment of ALS patients at the earliest referral: weight maintenance (if adequate) or gain (if underweight) is suggested from the scientific literature; evidence of improved diet quality (in terms of nutrients and limits for pro-inflammatory dietary factors) and glucose and lipid control is yet to be confirmed, but it is advised. Further research is warranted to better understand the role of nutrition and the underlying metabolic abnormalities in ALS, and their contribution to the pathogenic mechanisms leading to ALS initiation and progression.